2021
DOI: 10.1126/scitranslmed.abf0113
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell profiling of human bone marrow progenitors reveals mechanisms of failing erythropoiesis in Diamond-Blackfan anemia

Abstract: Ribosome dysfunction underlies the pathogenesis of many cancers and heritable ribosomopathies. Here, we investigate how mutations in either ribosomal protein large (RPL) or ribosomal protein small (RPS) subunit genes selectively affect erythroid progenitor development and clinical phenotypes in Diamond-Blackfan anemia (DBA), a rare ribosomopathy with limited therapeutic options. Using single-cell assays of patient-derived bone marrow, we delineated two distinct cellular trajectories segregating with ribosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 90 publications
4
48
0
Order By: Relevance
“…S5F ). Thus, while there is a large literature showing the specific importance of protein synthesis during erythropoiesis (Iskander et al, 2021; Khajuria et al, 2018; Vatikioti et al, 2019), our results highlight the importance of the cytoplasmic hypusine-dependent synthesis of the mitochondrial translation apparatus and thus, mitochondrial translation in erythroid differentiation.…”
Section: Resultssupporting
confidence: 49%
“…S5F ). Thus, while there is a large literature showing the specific importance of protein synthesis during erythropoiesis (Iskander et al, 2021; Khajuria et al, 2018; Vatikioti et al, 2019), our results highlight the importance of the cytoplasmic hypusine-dependent synthesis of the mitochondrial translation apparatus and thus, mitochondrial translation in erythroid differentiation.…”
Section: Resultssupporting
confidence: 49%
“…Mononuclear cells from normal donor peripheral blood were isolated by Ficoll-Hypaque (Sigma-Aldrich) density centrifugation following the manufacturer's instructions, as described before 26 . The mononuclear cell interphase layer was aspirated, washed with 1ml PBS, centrifuged at 300g for 5min and resuspended in 100μl PBS.…”
Section: Primary Samplesmentioning
confidence: 99%
“…Recent findings have suggested that erythropoiesis failure in DBA is more complicated than previously thought. More specifically, it seems that GATA1 impairment plays a crucial role in the DBA phenotype but only in ribosomal proteins of small-(RPS) and not large (RPL) subunit-related disorders [43].…”
Section: The Primary Defect In Dba Cellsmentioning
confidence: 99%
“…Furthermore, it seems that stress erythropoiesis impairment plays a crucial role mainly in RPL-related DBA, and its external stimulation by GC treatment may result in restoration of this pathway [43].…”
Section: Role Of Gcs In Cfu-e Precursorsmentioning
confidence: 99%